The Effect of Wind Speed on the Thermal Sensation in the Siti Walidah Building (Non-AC Area) - Muhammad Unggul Muhajiri Rahimi; Nur Rahmawati Syamsiyah; Muhammad Siam Priyono Nugroho (Urecol Journal. Part E: Engineering, 2021)
Thermal comfort is a necessity for an activity in a room, one of the parameters is wind speed. Wind speed is the speed of air flowing horizontally and vertically at an altitude above the ground. Wind speed is influenced by differences in temperature and air pressure as well as the characteristics of the surface on which it passes. Meanwhile, air that does not move in a closed room will cause the room user to feel uncomfortable. In this study, the object used is the Siti Walidah building, which is the main building, and is one of the service buildings belonging to the Muhammadiyah University of Surakarta. The object selection is based on the circular mosque shape, which is thought to affect the wind movement pattern. The purpose of this study was to determine the wind speed and the level of comfort of building users to the wind speed on each floor, especially in non-ac areas. The research method used is a quantitative approach with measurement and qualitative descriptive analysis, namely the interpretation of data because of observations, analysis with the surfer mapping program and interviews. This study also uses the SNI 03-6572-2001 reference. The results showed that the maximum comfort for users was felt only on the second floor with an average wind speed of 0.630 m/s in the morning and 1.139 m/s during the day. While the other floors have an average wind speed of below 0.25 m/s, which indicates that the wind category cannot be felt by the user.